A Novel Synthesis, Characterization and Performances of 1, 3, 5‐Trinitro‐2, 2‐bis(trifluoromethyl)‐1, 3, 5‐triazinane. Issue 20 (31st May 2019) - Yang, Tongtong; Xu, Zhibin; Meng, Zihui; Zhai, Lianjie
Abstract: A novel synthetic method of the 1, 3, 5‐trinitro‐2, 2‐bis(trifluoromethyl)‐1, 3, 5‐triazinane (2 ) has been successfully developed. In addition to IR, 1 H 13 C NMR and elemental analysis, compound 2 was characterized by 15 N NMR and X‐ray single crystal diffraction. Due to the introduction of trifluoromethyl, the density of compound 2 is up to 2.04 g⋅cm −3 at 298 K, which is consistent with its crystal density (2.059 g⋅cm −3, 296(2) K). Compound 2 exhibits excellent detonation pressures and velocities (P, 45.6 GPa; v D, 9564 m⋅s −1 ), as good as exceptional impact and friction sensitivities(IS, 22.5 J; FS, >360 J). Some of these values are better than the current benchmark explosives, such as 1, 3, 5‐trinitrodihydro‐1, 3, 5‐triazine (RDX) and cyclo‐1, 3, 5, 7‐tetramethylenene‐2, 4, 6, 8‐tetranitramine (HMX).It is a potential high energy density material. Abstract : We developed a novel synthetic method of the 1, 3, 5‐trinitro‐2, 2‐bis(trifluoromethyl)‐1, 3, 5‐triazinane (2) successfully in this work. Compound 2 exhibits good density (2.04 gcm −3 ), excellent detonation pressure and velocity (P, 45.6 GPa; v D, 9564 ms −1 ), as good as exceptional impact and friction sensitivity (IS, 22.5 J; FS, >360 J). Some of these values are better than the current benchmark explosives, such as 1, 3, 5‐trinitrodihydro‐1, 3, 5‐triazine (RDX) and cyclo‐1, 3, 5, 7‐tetramethylenene‐2, 4, 6, 8‐tetranitramine (HMX).